2015
DOI: 10.5455/medarh.2015.69.200-202
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Danger of Irrational Abusing Illegal Androgenic-anabolic Steroids in Recreational Athletes Age Under 35 in Bosnia and Herzegovina

Abstract: Introduction:Androgenic-anabolic steroids are rarely used by sportsmen who want to improve physical performance in competition sport. Despite that they are well aware of the side effects of anabolic steroids, many young athletes in Bosnia and Herzegovina without competition motivation come in temptation, trying to achieve better muscle proportion and physical performance unknowing consequence of side effects and what is hiding behind. Risk factors such as increasing of lipid levels and arterial hypertension ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…12 Data from a follow-up study, as reported by Pereira dos Santos et al, showed that these effects appeared to be relatively short lived; 13 currently there is a lack in evidence on the use of steroids in the longer term. A recent study reported the association between recreational of anabolic steroid use and arterial hypertension and hyperlipidemia; 14 Severo et al reported that changes in lipid profile, were associated to an increase in inflammatory markers and endothelial dysfunction. 15 In this case report, the side of the cerebral lesion was typical for a brain damage on hypertensive basis.…”
Section: Resultsmentioning
confidence: 99%
“…12 Data from a follow-up study, as reported by Pereira dos Santos et al, showed that these effects appeared to be relatively short lived; 13 currently there is a lack in evidence on the use of steroids in the longer term. A recent study reported the association between recreational of anabolic steroid use and arterial hypertension and hyperlipidemia; 14 Severo et al reported that changes in lipid profile, were associated to an increase in inflammatory markers and endothelial dysfunction. 15 In this case report, the side of the cerebral lesion was typical for a brain damage on hypertensive basis.…”
Section: Resultsmentioning
confidence: 99%
“…The biggest stimulus to scientific medical interest is the constant increase in the epidemiology of nutritional imbalance with the rise in hyperlipidemia. It is directly correlated with cardiovascular symptomatology, arterial hypertension, and the onset of type II diabetes as well as cardiovascular incidents in the younger population, at risk ages 18 to 35, and even below 18-year-olds who regularly abuse anabolic steroids [2][3][4][5][6][7][8] . Although many studies of anabolic steroids have focused predominantly on the onset of aggression towards others as well as criminal, asocial, delinquent behaviour, even suicidal behaviour, the scientific facts about automation in the misuse of consumption of anabolic preparations are poorly known [20][21][22][23][24][25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, a number of specific studies related to this substance are needed to statistically confirm the cause of health damage. and the question arises as to how many lives this underestimated epidemic will harm and take away [1][2][3][4][5] . We professionally believe that psychological support is needed in the form of stopping the consumption of anabolic steroids as well as additional measures to protect this young population group before the appearance of chronic cardiovascular symptoms as well as an incurable impairment of the mental state of consciousness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several resources have been used in order to gain muscle performance. Among them stands the use of steroids and anabolic agents, which, consumed in an indiscriminate, stimulates the development of diseases and increase the risk of death of its users 1,20 . In this perspective, the studies that use LLLT have been widely disseminated due the positive effects on muscle performance.…”
Section: Discussionmentioning
confidence: 99%